Retificador trifásico isolado em alta frequência para carregamento rápido de baterias de veículos elétricos - Bianchin, Carlos Gabriel (2017)
This work presents the development of a three-phase system for fast charging electric vehicle batteries, with high power factor, insulation at high frequency and low current stresses. The proposed system is based on a single-stage structure, by integrating the three-phase rectifier stage with a DC–DC converter isolated at high frequency. The proposed structure is based on the use of two sets of two levels bidirectional three-phase rectifiers operating with phase shift control between them. High–frequency transformer are inserted between the arms of each switching set, for a total of three transformers and a rectifier and a filter inductor on the output. This structure allows the use of classical PWM to control the input currents, obtaining high power factor, besides controlling the voltage of the primary bus. The phase shift control angle between the two rectifier modules allows to control the flow of power between the primary and the secondary bus, allowing independent control of the output current. The integrated operation of rectifier modules and high frequency transformers, allow to obtain some important operating characteristics such as reducted input current ripple and output by multi-phase operation of the rectifiers, division of the current efforts of the semiconductor between the input inductors and power division in the high-frequency transformers (important for operation with high power), single power processing stage with independent control of input and output currents, soft switching operation on most switches and possibility of bidirectional operation between the power grid and other DC source, such as photovoltaic panels, allowing the reduction of the impact of fast charge systems in the electrical system, and also enabling injection of energy in idle periods. his work presents the analysis of the topology, design and implementation of a 10 kW prototype for the fast charging batteries.